The determinants of profitability in the plantations and crops industry in Indonesian companies - Maria Dewinta Ture; Diyah Sukanti Cahyaningsih (Jurnal Penelitian, 2023)
This study aims to determine the effect of working capital turnover, company size, and sales growth on the profitability of plantation and food crop sub-industrial companies listed on the Indonesia Stock Exchange. This study employs quantitative analysis, utilizing financial data covering a five-year period for 25 listed companies. Company size is measured using total assets, while sales growth is evaluated based on the year-on-year revenue growth rate. Working capital turnover is calculated as the ratio of net sales to working capital. The findings reveal that firm size exhibits a significant negative effect on profitability, implying that larger firms may face challenges in optimizing cost efficiency. Conversely, sales growth shows a significant positive effect on profitability, this indicates that companies that experience higher revenue growth tend to achieve better profit margins. However, this research does not find a significant relationship between working capital turnover and profitability, which suggests that effective working capital management may not be an important determinant of profit margins in plantation and food crop sub-industry companies in the Indonesian market. These results provide valuable insights for investors, managers and policy makers in understanding the key drivers of profitability in this particular industry segment and can help make informed financial decisions.